Health, lifestyle, and quality of life for young adults born very preterm. Issue 3 (20th February 2004) - Cooke, R W I
Abstract : Background: Children born very preterm and able to attend mainstream schools have been shown to have a high prevalence of behavioural, minor motor, and learning difficulties. It is not clear whether these problems persist into adulthood, impacting on lifestyle and quality of life. Methods: A previously studied cohort of very low birth weight infants born between 1980 and 1983, together with term classmate controls, were assessed at age 19–22 years using a postal questionnaire. The questionnaire included the SF-36 to assess quality of life, a social activities scale, a lifestyle questionnaire, the Hospital Anxiety and Depression Scale, and questions on current height, weight, health, family structure, and education and occupation. Results: Of the 138 preterm and 163 term controls in the cohort, 79 preterm and 71 term returned questionnaires. Quality of life was assessed as similar on six of eight domains of the SF-36. Social activities were also similar. Preterms drank less alcohol, used fewer illicit drugs, but smoked as often. Rates for sexual intercourse were similar, although preterms had more children. Preterms were shorter than controls and were less satisfied with their appearance. They were more likely to use a regular prescription medicine. Fewer were or had been in higher education, and some remained unemployed. Conclusion: The problems experienced by very preterm infants at school appear to influence lifestyle and health, but not perceived quality of life in early adulthood.